Electromyographic activity of the ankle and foot during functional exercises and traditional exercises - Baldim, Isabella [UNESP] (2024)
Introduction: Traditional exercises using an elastic band are often standard in clinical practice to gain muscle strength. Additionally, functional exercises are considered more representative of functional tasks or sport. However, it is unclear whether functional exercises are comparable to traditional exercises in activating the ankle joint and foot. Objective: The purpose of this study was to analyze the effects of functional exercise and traditional exercise on the muscle activity of the ankle joint and foot. Methods: Thirty women participated in this study. Using surface electromyographic, muscle activation of the Tibialis Anterior (TA), Peroneus Longus (FL), Peroneus Short (FC), Gastrocnemius Medialis (GM) and Flexor Digitorum Shortus (FCD) was measured in nine exercises (dorsiflexion with an elastic band, plantar flexion with an elastic band, inversion with an elastic band, eversion with an elastic band, towel curl, standing plantar flexion, squats with an elastic band on the foot, diagonal propulsion and propulsion with peroneal stimulation). The muscle activation was normalized by the activation in maximum voluntary isometric contraction. Results: Functional exercises showed larger mean EMG amplitudes than the traditional exercises for all muscle groups (p > 0.05). Conclusion: Functional exercises provoked more activation compared with the traditional exercises. Functional exercises can be indicated to improve muscle function and functional task performance in populations that suffer dysfunction in ankle joint and foot.